The Awareness And Knowledge On Oral Cancer And Its Relation Towards Smoking Habit In Industrial Training Institute, Kepala Batas - Abdalla Musa, Reem Abdelgabar (2017)
Oral cancer is a worldwide health issue with increasing incidence annually as shown by a number of studies. In Malaysia, the prevalence of smoking and tobacco consuming is considerably high which unfortunately linked to fetal illness